DECODING DIFFICULTIES: STUDENTS’ PERFORMANCE IN TOEFL STRUCTURE AND WRITTEN EXPRESSION SECTION - Etika, Indah; Yuniko, Fajrilhuda (Universitas PGRI Sumatera Barat, 2025)
The TOEFL test is one of the graduation requirements at Universitas Syedza Saintika (UNSYKA), with a minimum score of 400 required for all study programs. However, some students have not yet been able to achieve this score. Preliminary research indicates that students in the Health Information Management Study Program at UNSYKA face difficulties in completing the Structure and Written Expression section of the TOEFL test. Therefore, this study aims to analyze the challenges students encounter, particularly from the material aspect. This research employs a descriptive method, with fifth-semester students from the Health Information Management Study Program in the 2021/2022 academic year as research subjects. Data were collected using two instruments: the researcher as the primary instrument and the Structure and Written Expression section of the TOEFL test. The findings revealed that 70.37% of students failed to achieve the university’s required minimum score of 400. Additionally, among the three sections of the TOEFL test, Structure and Written Expression proved to be the most challenging, with 44% of students obtaining the lowest scores in this section. Furthermore, among the eight material indicators tested, Inversion was found to be the most difficult, with a difficulty rate of 85.19%. Conjunctions ranked as the second most difficult indicator (80.22%), followed by Clauses and Phrases (64.07%). Basic Grammar Terminology was in fourth place (60.11%), followed by Expressions of Quantity (57.67%). Basic Sentence Patterns ranked sixth (57.02%). Meanwhile, Comparison had a difficulty level of 37.04%, and the easiest indicator was Unnecessary Words, with a percentage of 29.37%.